The Glutamate Receptor Plays a Role in Defense against Botrytis cinerea through Electrical Signaling in Tomato - Shuxian Feng; Caizhe Pan; Shuting Ding; Qiaomei Ma; Chaoyi Hu; Ping Wang; Kai Shi (Applied Sciences, 2021)
Plant glutamate-like receptor genes (GLRs) are homologous to mammalian ionotropic glutamate receptors genes (iGluRs). Although GLRs have been implicated in plant defenses to biotic stress, the relationship between GLR-mediated plant immunity against fungal pathogens and electrical signals remains poorly understood. Here, we found that pretreatment with a GLR inhibitor, 6,7-dinitriquinoxaline-2,3-dione (DNQX), increased the susceptibility of tomato plants to the necrotrophic fungal pathogen Botrytis cinerea. Assessment of the glr3.3, glr3.5 and glr3.3/glr3.5 double-mutants upon B. cinerea infection showed that tomato GLR3.3 and GLR3.5 are essential for plant immunity against B. cinerea, wherein GLR3.3 plays the main role. Analysis of the membrane potential changes induced by glutamate (Glu) or glycine (Gly) revealed that amplitude was significantly reduced by knocking out GLR3.3 in tomato. While treatment with Glu or Gly significantly increased immunity against B. cinerea in wild-type plants, this effect was significantly attenuated in glr3.3 mutants. Thus, our data demonstrate that GLR3.3- and GLR3.5-mediated plant immunity against B. cinerea is associated with electrical signals in tomato plants.